2015
DOI: 10.1016/j.mechmachtheory.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foot modelling on the human ankle kinematics and dynamics

Abstract: In this study, effects of some of the foot modelling assumptions on the ankle kinematics and dynamics are investigated based on the experimental data. For the kinematics analysis, the appropriateness of the stationary axis of rotation of the human ankle flexion is examined. Moreover, an interpolated function which is capable of predicting the directional changes of this axis is proposed. For the dynamics analysis, two main modelling assumptions of the number of the foot segments and the dimension of the foot m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it is clear that the point of application of these contact forces varies with time during the interaction between the foot and the ground along stance period. This issue is of paramount importance in order to obtain proper results, as it was demonstrated in [60][61][62]. Thus, in order to correctly define the point of application of reaction forces in the system, it is necessary to calculate the local coordinates of this point in relation to the center-of-mass of the foot [30].…”
Section: Model Developmetmentioning
confidence: 99%
“…Furthermore, it is clear that the point of application of these contact forces varies with time during the interaction between the foot and the ground along stance period. This issue is of paramount importance in order to obtain proper results, as it was demonstrated in [60][61][62]. Thus, in order to correctly define the point of application of reaction forces in the system, it is necessary to calculate the local coordinates of this point in relation to the center-of-mass of the foot [30].…”
Section: Model Developmetmentioning
confidence: 99%
“…Moreover, most studies use planar foot-ground contact models and rarely validate the results using real captures [63]. Therefore, finding a suitable foot-ground contact model for human motion simulation is currently an open research topic of great interest because in human motion analysis, the foot-ground contact model influences directly some results, like the ankle motion and torque, the ground-reaction forces and the muscle force estimates [91,92]. A good summary of published studies that use a foot-ground contact model can be found in [64].…”
Section: Foot-ground Contact Modellingmentioning
confidence: 99%
“…Different approaches that have been used in the literature can be found in Section 2.1.3. Finding a suitable foot-ground contact model for human motion simulation is currently an open research topic [91,92].…”
Section: Foot-ground and Crutch-ground Contact Model Calibrationmentioning
confidence: 99%